Prospects for Primary Stroke Prevention in Children with Sickle Cell Anaemia - Jordan, Lori C. (2012)
This review will focus on the strengths and limitations associated with the current standard of care for primary prevention of ischaemic strokes in children with sickle cell anaemia (SCA) - transcranial Doppler ultrasound (TCD) screening followed by regular blood transfusion therapy when TCD measurement is above a threshold defined by a randomized clinical trial (RCT). The theoretical basis for potential alternative strategies for primary prevention of neurological injury in SCA is also discussed. These strategies will include, but will not be limited to: immunizations to prevent bacterial infections, particularly in low income countries; management of elevated blood pressure; and targeted strategies to increase baseline haemoglobin levels with therapies such as hyroxycarbamide or potentially definitive haematopoietic stem cell transplant.